2013
DOI: 10.1016/j.jacc.2012.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atrial Fibrillation on Atrial Thrombogenesis in Humans: Impact of Rate and Rhythm

Abstract: Rapid atrial rates and AF in humans both result in increased platelet activation and thrombin generation. Prothrombotic activation occurs to a greater extent in the human LA compared with systemic circulation. AF additionally induces endothelial dysfunction and inflammation. These findings suggest that although rapid atrial rates increase the thrombogenic risk, AF may further potentiate this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(131 citation statements)
references
References 43 publications
6
112
1
10
Order By: Relevance
“…Samo AF może nasilać wiele z przedstawionych mechanizmów, co może tłumaczyć postępujący charakter arytmii; AngII -angiotensyna II; FIIa -trombina (czynnik IIa); FXII -czynnik XII; IL-6 -interleukina-6; TF -czynnik tkankowy; VCAM-1 -cząsteczka adhezyjna komórek naczyniowych typu 1 [80,105] przedsionka (LAA), stwarzają środowisko prozakrzepowe. Co więcej, nawet krótko trwające epizody AF prowadzą do uszkodzenia mięśnia przedsionków i ekspresji czynników prozakrzepowych na powierzchni śródbłonka przedsionków, a także aktywacji płytek i komórek zapalnych, przyczyniając się w ten sposób do uogólnionego stanu prozakrzepowego [88,89]. Ta przedsionkowa i układowa aktywacja układu krzepnięcia może częściowo tłumaczyć, dlaczego krótko trwające epizody AF wiążą się z długoterminowym ryzykiem udaru mózgu.…”
Section: Przebudowa Przedsionków a Czynność Kanałów Jonowychunclassified
“…Samo AF może nasilać wiele z przedstawionych mechanizmów, co może tłumaczyć postępujący charakter arytmii; AngII -angiotensyna II; FIIa -trombina (czynnik IIa); FXII -czynnik XII; IL-6 -interleukina-6; TF -czynnik tkankowy; VCAM-1 -cząsteczka adhezyjna komórek naczyniowych typu 1 [80,105] przedsionka (LAA), stwarzają środowisko prozakrzepowe. Co więcej, nawet krótko trwające epizody AF prowadzą do uszkodzenia mięśnia przedsionków i ekspresji czynników prozakrzepowych na powierzchni śródbłonka przedsionków, a także aktywacji płytek i komórek zapalnych, przyczyniając się w ten sposób do uogólnionego stanu prozakrzepowego [88,89]. Ta przedsionkowa i układowa aktywacja układu krzepnięcia może częściowo tłumaczyć, dlaczego krótko trwające epizody AF wiążą się z długoterminowym ryzykiem udaru mózgu.…”
Section: Przebudowa Przedsionków a Czynność Kanałów Jonowychunclassified
“…Fontan patients with AFF may be at higher risk of thromboembolism than Fontan patients without AFF due to a loss of atrial-ventricular synchrony, decreased systemic ventricular function (73.7% in our study), stasis in the systemic venous pathway, increased platelet activation through inflammation secondary to hypoxia (22), and, as suggested by accumulating evidence, a rapid atrial rate and rhythm associated with a pro-thrombotic state (23). Rates of systemic venous and arterial thromboembolic complications as high as 33% in Fontan patients have been reported, but the incidence of atrial flutter is unknown (2-11).…”
Section: Discussionmentioning
confidence: 57%
“…18 According to another report, AF led to not only local but also systemic endothelial dysfunction as assessed by levels of asymmetric dimethylarginine. 19 Additionally, Cai et al demonstrated that AF caused a marked decrease in endocardial NOS expression and NO bioavailability, and an increase in PAI-1 expression in the porcine LA. 20 These reports support the hypothesis that impaired atrial contraction induced by AF decreases the NO concentration and contributes to the thromboembolic phenomena in vivo.…”
Section: Discussionmentioning
confidence: 99%